Just War? War Games, War Crimes, and Game Design. Issue 4 (June 2019) - Donald, Iain
Military shooters have explored both historical and modern settings and remain one of the most popular game genres. While the violence of these games has been explored in multiple studies, the study of how war and the rules of war are represented is underexplored. The Red Cross has argued that as virtual war games are becoming closer to reality, the rules of war should be included. This article explores the argument put forward by the Red Cross and its reception by games media organizations, in order to consider how the concept of "just war" is represented within games. This article will focus on concerns over games adherence to the criteria of jus in bello (the right conduct in war) and will also consider the challenges that developers face in the creation of entertainment products in the face of publisher and press concerns.